The impact of high temperature and irradiance source on the efficiency of polycrystalline photovoltaic panel in a controlled environment - Julie C. Ogbulezie; Armstrong O. Njok; Manoj Kumar Panjwani; Suresh K. Panjwani (Institute of Advanced Engineering and Science, 2020)
Solar cells are highly sensitive to temperature, which affects its operating parameters. The study has its aim in accessing the impact of temperature (in excess above the maximum operating cell temperature) and irradiance source on the efficiency of polycrystalline photovoltaic (PV) solar panels in an environment where the temperature and irradiance level can be fully controlled. For the study to achieve its aim, a solar box and tungsten light bulbs were used to create an environment where the irradiance level and the temperature can be controlled. The solar panel was placed inside the solar box facing the light source while the irradiance level and temperature were measured and held constant. Results show a steady decrease in voltage with increasing temperature while the performance ratio and efficiency of the photovoltaic module followed a similar trend as that of voltage once the temperature exceeds the maximum operating cell temperature. Results also show the output voltage of the photovoltaic to be higher under the tungsten light than the sun, but the efficiency achieved by the photovoltaic under the sun far exceeds that obtained under the tungsten light.